Pengaruh Regulasi Emosi Terhadap Pengambilan Keputusan Bisnis dengan Family Values Sebagai Variabel Intervening - Irviana, Lala; Widhiastuti, Hardani; Pratiwi, Margaretha Maria Shinta; Dewi, Rusmalia (Dinasti Research, 2026)
The purpose of this study was to analyze the influence of emotional regulation on business decision-making with family values ​​as an intervening variable. Research can provide an overview of the importance of emotional regulation and strengthening family values ​​in the decision-making process, so that it can be used as a basis for maintaining the sustainability of family businesses and improving the quality of decisions across generations. The sample used was 100 FEB UNDIP students who are continuing their parents business. The data collection method used in this study was SEM PLS analysis tool with total 100 respondents. Data collection used questionnaires, namely the emotional regulation scale, decision-making scale, and family values ​​scale. The results of this study are emotional regulation on family values ​​of FEB UNDIP students, emotional regulation on decision making of FEB UNDIP students, family values ​​on decision making of FEB UNDIP students, and family values ​​mediate the influence of emotional regulation on decision making of FEB students UNDIP has a positive coefficient value (original sample). The implications of this study are related to decision-making behavior in the context of family businesses, especially among the younger generation and students. These findings support the psychological and behavioral perspectives in family businesses (Industrial and Organizational Psychology) that emphasize the role of emotional regulation and family values ​​as important mechanisms in the decision-making process.